Aging-Related Moderation of the Link Between Compliance With International Physical Activity Recommendations and the Hemodynamic, Structural, and Functional Arterial Status of 3,619 Subjects Aged 3–90 Years - Zócalo, Yanina; Gómez-García, Mariana; Torrado, Juan; Bia, Daniel (Frontiers in Sports and Active Living, 2022)
Background: Compliance with physical activity recommendations (CPAR) was associated with better health indicators. However, there are few studies to date that have comprehensively analyzed the association between CPAR and the cardiovascular status ´as a whole´ (e.g., analyzing hemodynamic, structural and functional properties, and different arterial territories). The relationship between CPAR and the cardiovascular properties could be strongly influenced by the growth and aging process. Aims: to investigate the association between CPAR and cardiovascular properties, by placing special emphasis on: (i) identifying if there is an independent association, (ii) if the association is 'moderated' by the age, and (iii) to what extent the association depends on the arterial parameter (hemodynamic vs. structural vs. functional) and/or the arterial segment (e.g., central vs. peripheral; elastic vs. transitional vs. muscular arteries). Methods: 3619 subjects (3-90 years) were studied. Extensive cardiovascular evaluations were performed. Cardiovascular risk factors (CRFs) and physical activity (PA) levels were determined. Subjects were categorized: compliant (n=1969) and non-compliant (n=1650) with World Health Organization-related PA recommendations. Correlation and multiple regression models (including CPAR*Age interaction) were obtained, and Johnson-Neyman technique was used to produce regions of significance. Results: The independent association between CPAR and cardiovascular characteristics were strongly moderated by the age. The moderation was observed for a wide age range, but particularly notorious for the extremes of life. Certain arterial characteristics demonstrated opposite effects in relation with CPAR status depending on the age range considered. Association between CPAR and cardiovascular characteristics was independent of CRFs and moderated by age. In subjects younger than 45-55 years, the CPAR status was associated with lower central and peripheral blood pressure (i.e., the younger the subject the higher the reduction). During adult life, as age increases in subjects, CPAR was associated with a beneficial hemodynamic profile, not related with variations in pressure, but strongly related with lower levels of waveform-derived indexes and ventricular afterload determinants. Conclusions: The independent associations between CPAR and arterial properties were strongly moderated by the age. Data provided by blood pressure levels and waveform-derived indexes would be enough to evaluate the independent association between CPAR and vascular system in the general population.